A New Visual Public-Key Cryptosystem Based On Non-Expansion Technique And Boolean Operations - Jaafar, Abdullah Mohammed Abdo Ali (2011)
Many public-key cryptosystems are used in our daily lives to attain privacy, authenticity, integrity and non-repudiation. However, most of the existing public-key algorithms are based on complex mathematical computations. Until recently, building a highly secured public-key cryptosystem without utilizing complex computations has been a serious challenge, making it necessary for investigations to develop new cryptography methods. Visual cryptography is special because the scheme requires visual inspection or the equivalence of simple Boolean computation and therefore, does not require complex computations. The basic design of visual cryptography exploits the human visual system, to recover secret images. Moreover, the visual inspection process could be carried out very easily by humans, but hard for the computer to imitate. Indirectly, such scheme adds extra protection to the visual scheme against brute-force search on the visual secret key.